2019
DOI: 10.1111/dmcn.14228
|View full text |Cite
|
Sign up to set email alerts
|

Treatment in childhood central nervous system demyelinating disorders

Abstract: The last two decades witnessed significant advances in the treatment of acquired demyelinating disorders: thirteen new agents have been approved for the treatment of multiple sclerosis in adults by the European Medicines Agency and US Food and Drug Administration in the last twenty years. Although the long‐term efficacy and safety profiles of some new drugs are still being assessed in paediatric MS, clinicians may have to use them in the management of paediatric onset MS resistant to first‐line medications, ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…We observed that most studies reported the use of IVIG over PLEX, but this might be due to the lack of availability of PLEX in several centres. One controversial topic is the oral corticosteroids tapering, as some experts suggest that the oral steroid tapering could prevent early relapses (Hennes et al, 2018;Konuskan and Anlar 2019) and others have concerns about a possible iatrogenic effect of steroid taper increasing the number of relapses by adrenal suppression especially in young children. Hacohen and Banwell (2019) There is no consensus regarding the use and type of the long-term maintenance treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that most studies reported the use of IVIG over PLEX, but this might be due to the lack of availability of PLEX in several centres. One controversial topic is the oral corticosteroids tapering, as some experts suggest that the oral steroid tapering could prevent early relapses (Hennes et al, 2018;Konuskan and Anlar 2019) and others have concerns about a possible iatrogenic effect of steroid taper increasing the number of relapses by adrenal suppression especially in young children. Hacohen and Banwell (2019) There is no consensus regarding the use and type of the long-term maintenance treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent review articles advocated for immunosuppressive therapies, such as mycophenolate mofetil, azathioprine, and anti-CD20 B-cell depleting therapies. Dale et al (2012) Konuskan and Anlar (2019) recommended mycophenolate mofetil or azathioprine as first line medications associated with low dose steroids or monthly IVIG until full efficacy and RTX or cyclophosphamide for severe or refractory cases. Hennes et al (2018) suggested that RTX and IVIG should be the initial choices.…”
Section: Review Of Expert Consensusmentioning
confidence: 99%
“…Only fingolimod and teriflunomide are approved in Europe for children. [33][34][35][36][37][38] Teriflunomide, fingolimod, dimethyl fumarate, rituximab, natalizumab, ocrelizumab, and alemtuzumab are used as primary/secondary or tertiary care in different positions in each country. Individualized treatment should also be considered in the POMS group.…”
Section: Treatments In Pediatric-onset Multiple Sclerosismentioning
confidence: 99%